STYLISTIC DEVICES IN ABDULHAMID CHULPON’S “KECHA VA KUNDUZ” (“NIGHT AND DAY”): A COMPARATIVE LINGUISTIC ANALYSIS OF THE ENGLISH TRANSLATION - Isakulova Rayxon Tulkin kizi; Khasanova Yulduz Mukhtor kizi (Bright Mind Publishing, 2025)
This study examines the extent to which stylistic devices in Abdulhamid Chulpon’s novel “Kecha va Kunduz” (“Night and Day”) have been preserved in Christopher Fort’s English translation. Drawing on translation studies and stylistic theories, this study analyzes how important artistic devices such as metaphor, simile, metonymy, and hyperbole are expressed in the translation. Based on a qualitative analytical methodology, the study conducts a comparative analysis of selected passages from the original text and the translated text, and examines the translator’s strategies and the degree of equivalence achieved. The results of the analysis show that while many stylistic devices have been preserved with a high degree of fidelity, some have been significantly altered or lost due to differences in language and culture. This study contributes to the broader academic discussion on literary translation, in particular by shedding light on how artistic expression is balanced across languages and cultures.